A foot tumour as late cutaneous Lyme borreliosis: a new entity?. (1st October 2017) - Bauvin, O.; Schmutz, J.‐L.; De Martino, S.; Busato, T.; Cribier, B.; Barbaud, A.; Wahl, D.; Bursztejn, A.‐C.
Summary: Acrodermatitis chronica atrophicans (ACA) is the late cutaneous form of Lyme borreliosis. The early inflammatory phase manifests with a bluish‐red discoloration and doughy swelling of the skin. The atrophic phase represents a late‐phase process with red discoloration, and a thin and wrinkled appearance of the skin. We present a patient who exhibited a previously undescribed form of late cutaneous Lyme borreliosis (LCLB) with a foot tumour. A 64‐year‐old woman had a large tumorous lesion on the right sole. The tumour size and deformation of the feet made wearing shoes difficult. On skin histology, a granulomatous lymphohistiocytic infiltrate with plasma cells was noticed. In fact, the patient recalled tick bites 2 or 3 years before. Borrelia burgdorferi (Bb) serology was highly positive and a polymerase chain reaction analysis on the skin biopsy detected Bb sensu lato, genospecies B. afzelii . We diagnosed LCLB and antibiotics were prescribed. On the more recent examination, the tumour had totally disappeared; the skin was atrophic and dry with only few scales. We report an atypical case of European LCLB, suggesting that ACA is not the only possible presentation of LCLB. The diagnosis of ACA is often clinically missed for months or years, and may be mistaken at the inflammation phase for vascular disorders, erysipelas or bursitis/arthritis, and at the atrophic phase for lichen sclerosus atrophicus, morphoea or anetoderma. To our knowledge, no such tumorous LCLB has previously been described.